Legal Analysis of Legal Protection Against Domestic Violence in Indonesia in 2025 - Hutama Prayogi; Erica Gita Pratiwi; Angela Merici Aristantri Rinjani; Akbar Habibul Rosyid; Malla Nadia Paramastri; Dea Nur Aeni; Mustafa (Journal of Creative Power and Ambition (JCPA), 2026)
Domestic Violence (DV) until 2025 remains a serious problem in Indonesia because it not only causes physical suffering, but also impacts the psychological, social, economic, and human rights conditions of victims. This study aims to analyze the legal form of legal protection for victims of domestic violence in Indonesia and identify various obstacles that affect the effectiveness of its implementation in law enforcement practices. The study uses a qualitative method with a normative legal approach through a literature study of laws and regulations, court decisions, scientific journals, and official reports of related institutions. The results of the study indicate that normatively legal protection for victims has been regulated through Law Number 23 of 2004 concerning the Elimination of Domestic Violence, the Law on Witness and Victim Protection, and various human rights instruments, but its implementation still faces obstacles in the form of patriarchal culture, low public legal awareness, economic dependence of victims, weak coordination between institutions, and the emergence of digital-based forms of violence in modern household relations. This study concludes that legal protection for victims of domestic violence requires an approach that is not only repressive, but also preventive, rehabilitative, and based on victim recovery so that legal protection can be more effective, responsive, and just.